Insulin Resistance and Dysregulation of Tryptophan–Kynurenine and Kynurenine–Nicotinamide Adenine Dinucleotide Metabolic Pathways - Oxenkrug, Gregory (Molecular neurobiology, 2013)
Insulin resistance (IR) underlines aging and aging-associated medical (diabetes, obesity, dyslipidemia, hypertension) and psychiatric (depression, cognitive decline) disorders. Molecular mechanisms of IR in genetically or metabolically predisposed individuals remain uncertain. Current review of the literature and our data presents the evidences that dysregulation of tryptophan (TRP)–kynurenine (KYN) and KYN–nicotinamide adenine dinucleotide (NAD) metabolic pathways is one of the mechanisms of IR. The first and rate-limiting step of TRP–KYN pathway is regulated by enzymes inducible by pro-inflammatory factors and/or stress hormones. The key enzymes of KYN–NAD pathway require pyridoxal-5-phosphate (P5P), an active form of vitamin B 6 , as a cofactor. Deficiency of P5P diverts KYN–NAD metabolism from production of NAD to the excessive formation of xanthurenic acid (XA). Human and experimental studies suggested that XA and some other KYN metabolites might impair production, release, and biological activity of insulin. We propose that one of the mechanisms of IR is inflammation- and/or stress-induced upregulation of TRP–KYN metabolism in combination with P5P deficiency-induced diversion of KYN–NAD metabolism towards formation of XA and other KYN derivatives affecting insulin activity. Monitoring of KYN/P5P status and formation of XA might help to identify subjects at risk for IR. Pharmacological regulation of the TRP–KYN and KYN–NAD pathways and maintaining of adequate vitamin B 6 status might contribute to prevention and treatment of IR in conditions associated with inflammation/stress-induced excessive production of KYN and deficiency of vitamin B 6 , e.g., type 2 diabetes, obesity, cardiovascular diseases, aging, menopause, pregnancy, and hepatitis C virus infection.